As parcerias público-privadas nas escolas públicas estaduais de Uberlândia (1995-2008) - Barbosa, Marília Guimarães Moreira (2009)
This study is inserted in the Line of Research named Politics and Management in Education, from the Program of Post-Graduation in Education, of the Federal University of Uberlândia. We investigate the public-private relation between the private initiative and the state schools of Basic Education of the City of Uberlândia-MG. The objective is to understand the logic of the capital in a macro reality, from the reform of the State in 1995, in the Management Shock in Minas Gerais, and the existing relation between the public-private spheres through the partnerships between the state schools and the private companies of Uberlândia. First we analyze the reconfiguration of the paper of the State by documentary and bibliographical research. Later we analyze the government Program Management Shock implemented in Minas Gerais for governor Aécio Neves, as politic, economic and social strategy that introduced in the education the form of proper management administration of neoliberal politics. We finish pondering on the cultures pertaining to school and enterprise, listing the main projects developed for the SEE/MG in partnership with the private initiative, confirming the approach of the public with the private one in the attempt to perceive the vision of the educational managers of Uberlândia regarding the partnerships between private initiative and State.